2013
DOI: 10.1002/mnfr.201300349
|View full text |Cite
|
Sign up to set email alerts
|

Dose–response plasma appearance of coffee chlorogenic and phenolic acids in adults

Abstract: This study confirmed previous findings about coffee bioavailability but also showed that coffee phenolics appear in a positive dose-response manner in plasma when drank at nutritionally relevant doses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
56
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 34 publications
5
56
0
Order By: Relevance
“…55,56 However, these beneficial effects could be limited by their bioavailability which is lower than methylxanthines, with phenolic plasma concentrations lower than 10 µM, depending of the degree of roasting and the consumed dose of coffee. 18,20 The results of this study showed a significant effect of 5-CQA on the modulation of platelet activation at 1 -20 µM, close to concentrations found in plasma after intake of green coffee extract (6 µM). 20 On the contrary, much higher doses of 3,5-DCQA, the other main polyphenol in green coffee and yerba mate, are needed (10 -20 µM) in order to significantly decrease ADP-induced P-selectin expression, much higher than the maximal plasma concentration (2.5 µM) reported for this compound.…”
Section: Effect On Fibrinogen Bindingsupporting
confidence: 74%
See 3 more Smart Citations
“…55,56 However, these beneficial effects could be limited by their bioavailability which is lower than methylxanthines, with phenolic plasma concentrations lower than 10 µM, depending of the degree of roasting and the consumed dose of coffee. 18,20 The results of this study showed a significant effect of 5-CQA on the modulation of platelet activation at 1 -20 µM, close to concentrations found in plasma after intake of green coffee extract (6 µM). 20 On the contrary, much higher doses of 3,5-DCQA, the other main polyphenol in green coffee and yerba mate, are needed (10 -20 µM) in order to significantly decrease ADP-induced P-selectin expression, much higher than the maximal plasma concentration (2.5 µM) reported for this compound.…”
Section: Effect On Fibrinogen Bindingsupporting
confidence: 74%
“…With respect to the metabolites of 5-CQA and 3,5-DCQA, only DHCA showed the ability to significantly modulate platelet activation at 1 µM, the maximal plasma concentration found after coffee intake. 18 We found that the colonic metabolites DHCA and DHFA significantly decreased P-selectin expression in ADP-stimulated platelets at 10 µM, with others showing a trend to decreased Pselectin expression on platelets activated by TRAP after incubation with DHCA. 57 On the contrary, concentrations of at least 100 µM were necessary to inhibit the expression of TRAP-and ADPinduced P-selectin by the early metabolites CA and FA, and 5-CQA, respectively, 42,58 while the 12 results of this study showed a significant decrease of ADP-induced P-selectin expression at noticeably lower concentrations (20, 10 and 1 µM for CA, FA and 5-CQA, respectively), indicating that the colonic metabolites may have an even stronger effect on platelet function than their phenolic precursors.…”
Section: Effect On Fibrinogen Bindingmentioning
confidence: 62%
See 2 more Smart Citations
“…7,8 The low nM levels of CQAs and FQAs in plasma is also supported by other studies which have involved enzymic deglucuronidation and desulfation of the plasma samples. 9 The aim of the current study was to expand the earlier work of Stalmach et al 7,8 and to investigate the impact on the plasma pharmacokinetic profiles and urinary excretion of chlorogenic acid-derived metabolites after the acute ingestion by human volunteers of three instant coffees containing 412, 635 and 795 mol of chlorogenic acids per 200 mL serving.…”
Section: Introductionmentioning
confidence: 98%